Going green: factors influencing hospitality students awareness / Fauzilatulanisa Noh, Wan Mahirah Wan Ibrahim and Salwa Mohd Hussin - Noh, Fauzilatulanisa; Wan Ibrahim, Wan Mahirah; Mohd Husssin, Salwa (Faculty of Hotel and Tourism Management, 2013)
Malaysia is one of the popular destinations of tourism in the worlds which it has been identified as ecological and cultural destinations. Because of that, the number of tourists had been increased and the tourism activities will relatively affect to environmental. This study focused on hospitality student’s awareness because they are the possibility as decision and policy maker in the future. The objective of the study is to examine the level of knowledge of green issues and factors influencing the green awareness. Pilot test among 30 Culinary Arts’s students in Universiti Tekhnologi Mara resulting moderate level of knowledge( Cronbach Alpha 0.637) while attitude (Cronbach Alpha 0.750) and finally Green awareness ( Cronbach Alpha 0.776) domains. A quantitative approach was the most suitable method of gathering data and information in order to obtain a meaningful data. A questionnaire was used to obtain respondents’ views about their knowledge towards a green concept. The study involved hospitality student’s final semester degree level of Faculty of Hotel and Tourism Management in Universiti Teknologi Mara, Shah Alam. A total of 325 questionnaires was successfully collected and 321 were found useful. Descriptive statistic, Pearson correlation, Reliability test, Independent T-Test, ANOVA and Multiple Regression were used to analyze the data. Based on the result, the highest standardized beta coefficient was attitudes towards the environment (β=. 297, p<. 05) and it was determined as the largest influence and makes the strongest contribution to explain on green awareness. In a conclusion, hopefully it could provide the academician and content expert to assist the students to overcome the issues.